Identifikasi Bahaya Menggunakan Metode HIRARC Pada Pekerjaan Pemeliharaan Gardu dan Jaringan Distribusi PT PLN UP3 Cengkareng - Della Putri Adjani; Restu Hikmah Ayu Murti (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
PT PLN is one of the largest companies providing electricity services in Indonesia. PT PLN is responsible for electricity generation, transmission, and distribution activities throughout Indonesia. This includes providing all electricity-related needs to the community. One of the activities is maintenance work on substations and distribution networks. As the largest electricity company in Indonesia, occupational safety is something that needs to be considered in all its activities. HIRARC is one of the methods used to prevent work accidents. HIRARC is a method used to identify dangers from an activity in a systematic and structured manner that can cause risks and explains how to control risks so that they do not cause losses. There were 6 sources of danger and 9 risks in concrete substation maintenance work and 8 sources of danger and 11 risks in low-voltage network maintenance work. Risk assessments for both concrete substation maintenance work and low-voltage network maintenance found 3 categories of danger, namely moderate, high, and extreme. After implementing risk control, it was found that all types of work were in the low category. This shows that the HIRARC method is quite effective in applying substation and distribution network maintenance work at PT PLN UP3 Cengkareng.